The institutionalisation and governance of village-owned enterprise in Indonesia for sustainable value creation / Rudy Suryanto - Suryanto, Rudy (2022)
Village-owned Enterprise (VOE) in Indonesia provides a promising contribution to the rural empowerment program in Indonesia. VOE was designed to create more jobs and help market Village products to solve the rampant problems of unemployment, poverty, and inequality in the villages. Despite the enormous funding and support, most VOEs do not perform well and fail to create social value. This study uses the New Institutional Theory and Institutional Analysis and Design (IAD) to underpin the emergence and development of VOE in Indonesia. This study aims to examine the institutional contexts of the emergence and development of VOE in Indonesia, investigate the business model, the governance and the sustainable value creation of VOE in Indonesia. This thesis used a qualitative study, specifically a single case study method in discussing the objectives. VOE Panggung Lestari the winner of the ASEAN Leadership Award 2019 in Social Change is chosen as a single case study.